ANIMATION VIDEO TO ENCOURAGE STUDENTS’ WRITING A STORY (NARRATIVE TEXT) IN INTENSIVE ENGLISH CLASSROOM - paria, Gus (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Media is one of excellent sources for helping students in learning. It is related incommunication and learning to transfer or deliver messages and it designed by the teacherand educator which should be enjoyable and meaningful for the students. There are manykinds of media that can be used for the teacher in helping the students, such as visual,audio, and audio-visual. Therefore, in order to help the students, the use of media isimportant.This paperis focused on the use of audio visual media that is animation videoinwriting a story inIntensive English classroom.The use of animation video offers manyadvantages for language learning. Animation video is a great medium in teaching,especially in teaching writing. This paper also describesthe theory of audio visual media(Animation Video)that can be used forstudents in writing class. The aim of this paper istoprovide several ways of teaching writing a story (Narrative Text) by using animationvideo that can be used for teacher in Intensive English classroomand to facilitatestudents’writing skill competence in English.Key words:Audio Visual Media, Intensive English Classroom, Animation Video, Writingskill